(untitled) (Jurnal Ilmu Gizi dan Dietetik, 2025)
Hospitals in general often face the problem of high soft diet food waste in hospitalized patients. This study aimed to analyze patient satisfaction with the taste and presentation of food and its relationship with the remaining soft diet food in the non-VIP inpatient room of Ciamis Hospital (RSUD Ciamis). This study used a cross-sectional design with 125 adult patients selected through quota sampling method. Satisfaction data was collected through a questionnaire modified from Hariez, while food waste was calculated using the food weighing method. Chi-Square test analysis. Most patients left little food (70.4%). The highest satisfaction in taste was aroma (87.2%), while the lowest was food temperature (34.4%). Cleanliness of cutlery had the highest satisfaction (99.2%), and timeliness of serving was the lowest (96.8%). There was a significant relationship between satisfaction with taste and food waste (p=0.012), but not with food presentation (p=0.886). The taste of food had a significant effect on patient food waste. The nutritional installation of RSUD Ciamis needs to keep the food temperature stable during distribution to increase patient satisfaction.